Diabetes Prevention in the New York City Sikh Asian Indian Community: A Pilot Study - Nadia S. Islam (International Journal of Environmental Research and Public Health, 2014)
India has one of the highest burdens of diabetes worldwide, and rates of diabetes are also high among Asian Indian immigrants that have migrated into the United States (U.S.). Sikhs represent a significant portion of Asian Indians in the U.S. Diabetes prevention programs have shown the benefits of using lifestyle intervention to reduce diabetes risk, yet there have been no culturally-tailored programs for diabetes prevention in the Sikh community. Using a quasi-experimental two-arm design, 126 Sikh Asian Indians living in New York City were enrolled in a six-workshop intervention led by community health workers. A total of 108 participants completed baseline and 6-month follow-up surveys between March 2012 and October 2013. Main outcome measures included clinical variables (weight, body mass index (BMI), waist circumference, blood pressure, glucose, and cholesterol) and health behaviors (changes in physical activity, food behaviors, and diabetes knowledge). Changes were significant for the treatment group in weight, BMI, waist circumference, blood pressure, glucose, physical activity, food behaviors, and diabetes knowledge, and between group differences were significant for glucose, diabetes knowledge, portion control, and physical activity social interaction. Retention rates were high. Findings demonstrate that a diabetes prevention program in the Sikh community is acceptable, feasible, and efficacious.